Salty, spiced, and a little bit nice - Timoti, Cynthia (Tom Doherty Associates/Tor Publishing Group, 2025)
"Ellie Pang has had enough of her controlling family​ who has been micromanaging her life since her type 1 diabetes diagnosis​. When her parents orchestrate a public proposal from their business partner's son, a proposal that goes humiliatingly viral, Ellie escapes to the other side of the country to put her dream of opening a sugar-free bakery into action. After all, she'd done her research. How hard can it be? She hits a snag when her storefront turns out to be a dump and in need of major renovations. Worse, the only person who can help her turn things around is Alec Mackenzie, her brother's best friend and the man responsible for crushing her teenage heart ten years ago. But Alec has a proposal of his own: he needs a pretend girlfriend in order to cement a business deal. All they need to do is feign love and affection, while trying not to maim each other. As the thin line between hate and fake-madly-in-love starts to blur, buried secrets resurface, and Ellie must learn to trust her heart."--Amazon.